Government Health Expenditures on Economic Growth in ASEAN-9 Countries - Qurrota A'yun, Indanazulfa; Irwandi (Forum Kerjasama Pendidikan Tinggi, 2022)
Government expenditure is one of the part of fiscal policy that governs the economy for the realization of people's welfare and the stability of economic activity. One of the government expenditures is used for the health sector, where health is one of important indicator as an effort in realizing public health development. Accordingly, this study aims to analyze the effect of government health expenditure on economic growth in ASEAN-9 countries. This paper based on panel data of a sample of 9 countries in ASEAN that consist of Indonesia, Malaysia, Singapore, Thailand, Philippines, Brunei Darussalam, Myanmar and Cambodia, using data for the period 2000-2019. The best selection model in this paper is fixed effect model. Empirical results find that health expenditure of GDP have a positive effect to economic growth. Then, the health expenditure of pocket and population have a negative significant effect on economic growth. However, the health expenditure per capita and health expenditure government have no significant effect on economic growth. This suggests that there needs to be an increased of focus on investment and the speed of developing medical services and public health efficiency so as to improve public health and economic growth.